R for Stata Users - Muenchen, Robert A.; Hilbe, Joseph M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Stata is the most flexible and extensible data analysis package available from a commercial vendor. R is a similarly flexible free and open source package for data analysis, with over 3,000 add-on packages available. This book shows you how to extend the power of Stata through the use of R. It introduces R using Stata terminology with which you are already familiar. It steps through more than 30 programs written in both languages, comparing and contrasting the two packages' different approaches. When finished, you will be able to use R in conjunction with Stata, or separately, to import data, manage and transform it, create publication quality graphics, and perform basic statistical analyses. A glossary defines over 50 R terms using Stata jargon and again using more formal R terminology. The table of contents and index allow you to find equivalent R functions by looking up Stata commands and vice versa. The example programs and practice datasets for both R and Stata are available for download. Robert A. Muenchen is the author of the book, R for SAS and SPSS Users, and is a consulting statistician with 29 years of experience. He has served on the advisory boards of SAS Institute, SPSS Inc., and the Statistical Graphics Corporation. He currently manages Research Computing Support at The University of Tennessee. Joseph M. Hilbe is Solar System Ambassador with NASA/Jet Propulsion Laboratory, California Institute of Technology, an adjunct professor of statistics at Arizona State, and emeritus professor at the University of Hawaii. He is a Fellow of the American Statistical Association and elected member of the International Statistical Institute. Hilbe was the first editor of the Stata Technical Bulletin, (later named the Stata Journal) and is author of a number of textbooks, including Logistic Regression Models and Negative Binomial Regression.
Installing and Updating R -- Running R -- Help and Documentation -- Programming Language Basics -- Data Acquisition -- Selecting Variables -- Selecting Observations -- Selecting Variables and Observations -- Data Management -- Enhancing Your Output -- Generating Data -- Managing Your Files and Workspace -- Graphics Overview -- Traditional Graphics -- Graphics with ggplot2 -- Statistics -- Conclusion.
Keywords: Statistics .; Statistics and Computing/Statistics Programs